A case study on fraudulent financial reporting: evidence from Malaysia. Issue 1 (3rd May 2016) - Lau, Chee Kwong; Ooi, Ki Wei
Abstract : Purpose: This paper aims to examine cases of fraudulent financial reporting (FFR) which were subject to published enforcement actions by the Securities Commission Malaysia (SC) from 1998 to 2012 for reasons of alleged financial misreporting. It investigates the main attempts used (how) and sensible motives (why) for these fraudulent reporting. Design/methodology/approach: This study undertakes a close examination of the financial reports manipulated – annual accounts, interim reports and financial reports in listing proposals, initial public offering prospectuses and corporate restructuring proposals. Due to the limited number of FFR published, a close examination of these cases is the best way to reach a more comprehensive and detailed understanding of "how" FFR takes place, rather than performing large sample statistical analyses. This study also collects data which provide evidence for the possible motivations in resorting to the FFR. Findings: The most common attempt used by the sample companies was to overstate their reported revenue by recognising fictitious sales from bogus customers. Sample companies who attempted this initial manipulation often followed with consequential manipulations and in some cases also embarked on masking manipulations. Sensible motives for the sample companies to manipulate their financial statements include capital raising exercises, closeness to defaulting on debt repayments and sustaining equity overvaluations. Research limitations/implications: The primary limitation of this study is its lack of breadth due to the limited number of reported cases available. Moreover, taking the sample companies used from enforcement action releases published by the SC presupposes that the SC has diligently and correctly identified all the FFR cases – whereas there is a possibility that some companies involved in FFR may not yet have been detected or publicly revealed. Notwithstanding these limitations, our findings provide a comprehensive insight, which is sufficient in depth, into the operational aspects of FFR in Malaysia. Practical implications: One practical lesson from the findings on "how" within the chain of manipulations is that auditors ought to review the effectiveness of their analytical and substantive procedures, as a number of the FFR cases remained undetected by the audit process. A second is that accounting standards setters may wish to reconsider the amount of discretion given to managers in financial reporting. On the one hand, some managers have used this discretion to provide useful information to the market; however, others have opportunistically used it for personal gain. Social implications: From the societal perspective, it is time for managers, as agents of capital providers, to self-review their responsibilities and stewardship in financial reporting. There needs to be a paradigm shift in their attitudes towards the perceived incentives of, and opportunities for, FFR. Managers' wrongdoings in these accounting scandals have had significant adverse consequences for society – including minority shareholders, investor confidence, future accountants and managers in the making. Originality/value: This study provides direct and practical evidence on the "how" and "why" of FFR in the context of a developing country – Malaysia. Such evidence is limited in the existing literature and relevant to practitioners.